New detectors for electron microscopy - Clough, R; Robert N. Clough (2015)
Detectors for Electron Microscopy have traditionally used a scintillator to generate photons from fast electrons, which are then detected by a sensor. However, in recent years direct detection has become an area of interest due to the potential improvements to detector performance. In this thesis various aspects of direct detection are presented. I will begin with simulations of direct detectors based on Joy’s model of straight trajectories between Rutherford scattering events, where signal is generated by inelastic scattering events. The effects of microscope operating voltage, detector thickness, a surface electrically dead layer and diode depth on detector performance are presented. A prototype detector was developed using the DUOS sensor, two thicknesses of the sensor were produced a 50μm thick detector and a 20μm thick detector. EBSD results are presented which show how the use of a reactive ion etch to reduce the dead layer thickness of a mechanically thinned sensor improve the detection efficiency of a sensor allowing EBSD work to be carried out at operating voltages as low as 5keV. The MTF and DQE of both thicknesses of DUOS sensor are measured at 80kV and 200kV, which show that there is little difference between the two thicknesses at 80kV, but at 200kV the thinner detector shows an improved MTF. The results are then and compared with the equivalent simulated detectors. I show how the high frame rate of a detector and rigid and non-rigid registration can be used to improve image quality, resolving the {331} lattice spacing which is not visible with a simple summation of frames. Detectors using gallium nitride rather than silicon as the base semiconductor are simulated. The MTF at the Nyquist frequency for a GaN detector is double that of a Si detector at an operating voltages of 80kV due to the smaller interaction volume of an electron in GaN. However, at higher voltages the improvement is much smaller as most electrons pass through the detector.